The Most Successful Works Performed in The Years of Independence - Abiyev Sultanbek Kalbayevich (Zien Journals, 2022)
It is known that the theater has long been a center of education, and today it is honorably fulfilling its eternal mission. This can be seen in the growing interest of the audience in theatrical art. Over the years, theatrical art has traversed the path of centuries-old development and has produced a wide range of artists who are recognized by many. The following article is devoted to the successful works of art performed during the years of independence
Keywords: modernity; audience; repertoire; opera